2016
DOI: 10.1007/s10661-016-5204-8
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of digital soil mapping to predict soil properties over low-relief areas

Abstract: This study investigates the ability of different digital soil mapping (DSM) approaches to predict some of physical and chemical topsoil properties in the Shahrekord plain of Chaharmahal-Va-Bakhtiari province, Iran. According to a semi-detailed soil survey, 120 soil samples were collected from 0 to 30 cm depth with approximate distance of 750 m. Particle size distribution, coarse fragments (CFs), electrical conductivity (EC), pH, organic carbon (OC), and calcium carbonate equivalent (CCE) were determined. Four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(63 citation statements)
references
References 32 publications
5
56
2
Order By: Relevance
“…BRTs generally avoid overfitting [35], can be applied to a variety of spatial analyses, such as the distribution of species and vegetation types [36][37][38][39][40][41][42], hydrology [43,44], soil and landform properties [45][46][47] and natural disturbance [48], as well as quantification of land cover and land use change through human activities [34,49,50]. Across a wide variety of contexts, model comparisons have shown BRTs to perform much better than traditional models and comparably well to other machine-learning models [36,37,43,45,48,51], with some variability in comparative performance with other machine-learning methods depending on context [33,38,44,47].…”
Section: Discussionmentioning
confidence: 99%
“…BRTs generally avoid overfitting [35], can be applied to a variety of spatial analyses, such as the distribution of species and vegetation types [36][37][38][39][40][41][42], hydrology [43,44], soil and landform properties [45][46][47] and natural disturbance [48], as well as quantification of land cover and land use change through human activities [34,49,50]. Across a wide variety of contexts, model comparisons have shown BRTs to perform much better than traditional models and comparably well to other machine-learning models [36,37,43,45,48,51], with some variability in comparative performance with other machine-learning methods depending on context [33,38,44,47].…”
Section: Discussionmentioning
confidence: 99%
“…From this DEM, 9 terrain variables commonly used for predictions and mapping of soil classes and properties [10,[50][51][52][53][54][55] were selected using both ArcGIS 10.1 and SAGA GIS [56], including: slope, topographic wetness index (TWI), SAGA wetness index (SWI), cross-sectional and longitudinal curvatures, vertical distance to channel network and valley depth, in addition to elevation and Geomorphons [57]. Geomorphons consist of an algorithm that classifies the landscape into 10 possible landforms, and thus, it is expected to contribute to distinguishing geomorphology patterns that may be related to varying soil classes and properties.…”
Section: Soil Classes Mappingmentioning
confidence: 99%
“…Even though sample size is not the only factor affecting R 2 when comparing different studies, a notable pattern can be observed. For example, comparing two studies predicting calcium carbonate equivalent (CCE) using MLR, the R 2 of independent validation improved from 0.06 with 120 observations [55] to 0.51 with 137 observation [56]. In those same studies, the R 2 for independent validation increased from 0.05 to 0.40 for predicting sand content.…”
Section: Sample Sizementioning
confidence: 99%
“…The same pattern is seen for other soil properties. Mosleh et al [55] predicted soil organic carbon (SOC) with an R 2 of 0.26 for independent validation. Bonfatti et al [26] predicted SOC with 43 more samples than Mosleh et al.…”
Section: Sample Sizementioning
confidence: 99%